Developments in the systemic treatment of metastatic cervical cancer - Mountzios, G.; Soultati, A.; Pectasides, D.; Pectasides, E.; Dimopoulos, M.-A.; Papadimitriou, C.A. (Cancer Treatment Reviews, 2013)
Despite the available prevention and early detection strategies, advanced squamous-cell carcinoma of the uterine cervix remains a major concern for public health. Systemic treatment with cisplatin, either in combination with external beam irradiation for locally advanced disease, or as monotherapy for recurrent/metastatic disease has been the cornerstone of treatment for more than two decades. Cisplatin has been also combined with a number of agents including paclitaxel, topotecan, gemcitabine, vinorelbine and ifosfamide, leading to encouraging response rates and increases in progression-free survival in a series of randomized phase III trials. Platinum-based triplets have been also tested, albeit at the cost of substantial toxicity. More recently, combinations with molecular agents targeting critical pathways in cervical malignant transformation are being assessed in clinical trials. In the current review, we discuss all recent advances in the systemic treatment of metastatic cervical cancer with emphasis on the results of large randomized phase III trials. Concerns regarding treatment-related toxicity in the context of co-morbidities and the need for potent predictive biomarkers for individualized treatment are also addressed. © 2012 Elsevier Ltd.
Keywords: Cervical cancer; Chemotherapy; Metastatic; Prognostic and predictive markers; Systemic therapy; targeted therapy; Toxicity